Inter-maceral effects on hydrocarbon generation as determined using artificial mixtures of purified macerals. (June 2020) - Xie, Xiaomin; Snowdon, Lloyd R.; Volkman, John K.; Li, Maowen; Xu, Jin; Qin, Jianzhong
Highlights: Rock-Eval and FT-IR characteristics of maceral mixtures fit with calculated values. C2 –C4 hydrocarbons and gas–oil ratios of mixtures were close to expected values. Even a low algal organic matter content dominates the Py-GC HC distribution. A low proportion of vitrinite among the macerals yields more C15+ than expected. Abstract: Different proportions of purified, low maturity maceral concentrates (∼0.4 %Ro) have been artificially mixed to evaluate changes in the hydrocarbon generation characteristics as a function of maceral-maceral interactions. The purified maceral concentrates (lamalginite [L], detrovitrinite [D] and resinite [R]) were obtained from an Eocene lacustrine oil shale and an Eocene coal sample from NE China. Four artificial mixtures (L:D:R = 80:20:0 wt%, 50:50:0 wt%, 70:25:5 wt%, and 20:80:0 wt% were prepared for analysis. Comparison of the measured and calculated geochemical parameters of artificial mixtures shows that bulk characteristics such as Rock-Eval data, carbon isotope values, Fourier transform infrared (FTIR) parameters, the Py-GC gaseous hydrocarbon content and gas–oil ratios of the maceral mixtures are consistent with the calculated values. However, the Py-GC hydrocarbon distribution patterns of the liquid oil (C5-14 ) and C15+ fractions show deviations from the expected values. In particular, the Py-GC distribution pattern and n -alkene/ n -alkane pattern of the mixtures are similar to that of the purified lamalginite maceral concentrate, even when the lamalginite content in the mixture is low (i.e. 20%). Py-GC of the mixtures with detrovitrinite yields much more of the C15+ fraction than calculated and the deviation is larger in mixtures with a smaller amount of detrovitrinite. It is apparent that the alginite maceral is the main source of hydrocarbons and will strongly influence the hydrocarbon distribution pattern, while the presence of vitrinite could lead to enhanced C15+ hydrocarbon amounts. These results suggest that geochemical properties and generated hydrocarbon amounts can be influenced by the interaction of different organic matter types. Further research is needed to determine the specific chemical/physical nature of these interactions.